DETERMINAN YANG MEMPENGARUHI KINERJA KARYAWAN PADA PT. NUSANTARA SUKSES BETON - Lastri Anggi Fani; Indra Firdiyansyah (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
This research aims to determine the effect of conflict and work environment either partially or simultaneously on employee performance at PT. Nusantara Sukses Beton. This research is a quantitative research. The subject of this research is employees of PT. Nusantara Sukses Beton with a sample of 16 people. Data collection using questionnaires that have been tested for validity and reliability. The result of the research shows that there is no positive and significant influence between conflict and employee performance with the result of t test. With a value of 0.492 t count is greater than t table 3.81 with a significant value of 0.631, this value is greater than 0.05. There is no positive and significant influence between work environment and employee performance with the result of t test. With t count value 2.356 bigger than t table 3.81 with significant value 0.03, this value is smaller than 0.05. There is a positive and significant influence between conflict and work environment simultaneously on the performance of employees in targeted with test results f. With the f value of 6,602 is smaller than f table 3.18.